2020
DOI: 10.1177/0300060520918781
|View full text |Cite
|
Sign up to set email alerts
|

Use of double-J ureteric stents post-laparoscopic pyeloplasty to treat ureteropelvic junction obstruction in hydronephrosis for pediatric patients: a single-center experience

Abstract: Objectives We aimed to investigate the safety concerns associated with placing double-J ureteric stents post-laparoscopic pyeloplasty surgery for congenital ureteropelvic junction obstruction (UPJO) and hydronephrosis. Methods A total of 1349 patients with postoperative double-J stent placement at our center were included. Clinical variables for enrolled patients were collected by two independent authors. We compared clinical variables and the efficacy of stenting post-laparoscopic pyeloplasty. Results The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…No significant differences were observed in other types of complications such as UTI, stent displacement, and postoperative recurrence. This is consistent with other similar studies ( 15 , 16 ), so the cost of stent-less pyeloplasty is an unavoidable high incidence of urinary leakage. Unfortunately, almost all postoperative urine leakage needs to be treated by intubation; it means that reoperation is conducted within a short period of time after the first surgery, which is unacceptable for children and their parents, and it may cause doctor–patient conflict and bring great challenges to clinical work.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No significant differences were observed in other types of complications such as UTI, stent displacement, and postoperative recurrence. This is consistent with other similar studies ( 15 , 16 ), so the cost of stent-less pyeloplasty is an unavoidable high incidence of urinary leakage. Unfortunately, almost all postoperative urine leakage needs to be treated by intubation; it means that reoperation is conducted within a short period of time after the first surgery, which is unacceptable for children and their parents, and it may cause doctor–patient conflict and bring great challenges to clinical work.…”
Section: Discussionsupporting
confidence: 93%
“…Combined with the above discussions, we find that stent-less pyeloplasty is the most minimally invasive, but it has a high incidence of urinary leakage. Combined with the results of the other studies (5,6,10,(15)(16)(17), we found that the advantages of the DJ stent are that it is safe, reliable, effective, and more minimally invasive, while the removal time of the PU stent is shorter, which can reduce the occurrence of catheter-related complications. And the disadvantages are obvious too, such as issues with anesthesia during DJ stent removal and the high risk of urine leakage associated with the PU stent.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…UPJO is a common disease in pediatric urology with an incidence of about 1/2,000 in newborns, and the ratio of the men to women is 2~3:1 ( 20 ). UPJO usually reduces the free flow of urine from the renal pelvis to the ureter, causing dilation of the renal pelvis and calyces and hydronephrosis ( 21 ). Ureteropelvic junction stenosis, crossing vessel, and ureteropelvic junction valve and stone are also important causes of UPJO.…”
Section: Discussionmentioning
confidence: 99%
“…Finding of higher incidence rate of septicemia in PCN than DJS is in accordance with a previous similar work 20 indicating some loopholes in the PCN. Stent migration 21 or encrustation can be expected in DJS for ureteral obstruction but total failure of this procedure is a rare one while advanced stage of the causative agent e.g., malignancy cannot be ruled out in the context. The failure needs readdress of the issue for complete relief otherwise patient shifts to bad experience of hemodialysis 22 using various devices.…”
Section: Discussionmentioning
confidence: 99%